Precision biomaterials in cancer theranostics and modelling - Caballero, David (2022)
Despite significant achievements in the understanding and treatment of cancer, it remains a major burden. Traditional therapeutic approaches based on the 'one-size-fits-all' paradigm are becoming obsolete, as demonstrated by the increasing number of patients failing to respond to treatments. In contrast, more precise approaches based on individualized genetic profiling of tumors have already demonstrated their potential. However, even more personalized treatments display shortcomings mainly associated with systemic delivery, such as low local drug efficacy or specificity. A large amount of effort is currently being invested in developing precision medicine-based strategies for improving the efficiency of cancer theranostics and modelling, which are envisioned to be more accurate, standardized, localized, and less expensive. To this end, interdisciplinary research fields, such as biomedicine, material sciences, pharmacology, chemistry, tissue engineering, and nanotechnology, must converge for boosting the precision cancer ecosystem. In this regard, precision biomaterials have emerged as a promising strategy to detect, model, and treat cancer more efficiently. These are defined as those biomaterials precisely engineered with specific theranostic functions and bioactive components, with the possibility to be tailored to the cancer patient needs, thus having a vast potential in the increasing demand for more efficient treatments. In this review, we discuss the latest advances in the field of precision biomaterials in cancer research, which are expected to revolutionize disease management, focusing on their uses for cancer modelling, detection, and therapeutic applications. We finally comment on the needed requirements to accelerate their application in the clinic to improve cancer patient prognosis.